Peningkatan Kesiapsiagaan Siswa Sekolah Dasar dalam Menghadapi Bahaya Gempa Bumi dan Tsunami - Munandar, Aris; Suhardjo, Suhardjo; Lestariningsih, Dwi Sukanti; Hardi, Ode Sofyan (Jurnal SOLMA, 2019)
The purpose of this activity is 1). Provide a correct understanding of the types of disasters, places to save themselves when a disaster occurs. 2) Perform a self-rescue simulation when a disaster occurs. The objectives in this activity are students in 3 schools that have high risk namely SD 1,2 and 3 Sawarna Bayah District. Lebak Banten The number of participants was 35 students consisting of 20 female students and 15 male students. The implementation activity is divided into 3 , namely the transfer knowledge, games, and simulations. Submission of material includes: video screening, giving quizzes. Video shows contain an introduction to the types of disasters, namely: earthquakes, tsunamis, landslides, floods, hurricanes / typhoons, fires, volcanic eruptions. The next material is in the form of safe locations when the disaster occurs. Vidoe describes which locations should be addressed and avoided. After the video was aired, an evaluation of the extent of understanding of threatening environmental disasters was carried out. The game is done by classifying types of disasters. The last activity is a simulation when an earthquake occurs using singing. In general, the results of evaluation and simulation results can run according to the objectives. Participants can understand the types of disasters, disasters that may occur in their environment, can understand the destination when an earthquake or tsunami occurs. Participants can take part in the simulation while singing. The hope after getting the right understanding can be transmitted to other friends, as well as family and society in general. There needs to be broader socialization to other students given the threat of tsunami threatening in three schools. Socialization is in the form of posting posters / images about the types of hazards and efforts to save themselves in the event of a disaster.